Wave modelling in coastal and inner seas. (October 2018) - Cavaleri, L.; Abdalla, S.; Benetazzo, A.; Bertotti, L.; Bidlot, J.-R.; Breivik, Ø.; Carniel, S.; Jensen, R.E.; Portilla-Yandun, J.; Rogers, W.E.; Roland, A.; Sanchez-Arcilla, A.; et al.
Highlights: A summary of the present state of the art in enclosed sea wave modelling. Many examples of present modelling capability and limitations. A deep discussion and analysis of wave-current interactions and modelling. A discussion of the present state of the art in wave modelling. A look and a prospect for the corresponding possible future developments. Abstract: In the long term development of the research on wind waves and their modelling, in particular of the inner and coastal seas, the present situation is framed with a short look at the past, a critical analysis of the present capabilities and a foresight of where the field is likely to go. After a short introduction, Chapter 2 deals with the basic processes at work and their modelling aspects. Chapter 3 highlights the interaction with wind and currents. Chapter 4 stresses the need for a more complete, spectral, approach in data assimilation. Chapter 5 summarizes the situation with a discussion on the present status in wave modelling and a look at what we can expect in the future.